EFEK HEPATOPROTEKTIF DAN NEFROPROTEKTIF BIJI ALPUKAT PADA TIKUS TERINDUKSI KARBON TETRAKLORIDA - Phebe Hendra; Gidion Krisnadi; Ni Luh Putu Dian Perwita; Ike Kumalasari; Yuditha Anggarhani Quraisyin (Faculty of Pharmacy, Universitas Gadjah Mada, 2014)
The aim of this research to investigate the hepatoprotective and nephroprotecitve effects of Avocado seeds against carbon tetrachloride in rats. The rats was treated with the infusion and decoction of avocado seeds at doses 360.7, 642.1, 1142,9 mg/kg per oral once in a day for 6 days and carbon tetrachloride (2mL/kg) was given on the 7th day. Blood sample from all groups was obtained by sinus orbitalis after 24 hours application for the serum transaminase and creatinine. The increasing of serum transaminase and creatinine in carbon tetrachloride-treated rats, were significantly decreased (p<0.05) with both pretreatment of infusion and decoction of avocado seeds. Based on the research, it can be concluded that infusion and decoction of avocado seeds have a potent protective action upon carbon tetrachloride-induced hepatic and renal damage in rats.